Angelabella tecomae (Lepidoptera: Gracillariidae): an exotic hostplant in northern Chile and first record from Peru - VARGAS, HÉCTOR A. (Revista Colombiana de Entomología, 2010)
Tecoma stans (Bignoniaceae), an exotic ornamental tree, is mentioned for the first time as a host for larvae of Angelabella tecomae (Lepidoptera: Gracillariidae) in northern Chile. The presence of A. tecomae is reported for the first time from the coastal desert of southern Peru.